Estudio de calidad de energía en el taller de metalmecánica de la empresa multiproyectos electromecánicos Ltda. (2023)
This project describes the disturbances that generate distortion to the electric power signals and that are taken into account in the study and monitoring of CEL Electric Power Quality; For this reason, a methodology and procedure is proposed for the measurement and recording of these parameters obtained by a network analyzer, relating the entire process with the national and international regulations and regulations in force in Colombia